2019
DOI: 10.1111/ejss.12849
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and precipitation of myo‐inositol hexakisphosphate onto kaolinite

Abstract: Sorption of myo‐inositol hexakisphosphate (IHP), a common type of organic phosphorus in soils, largely controls its mobility and bioavailability. Research on the interaction between IHP and phyllosilicate minerals such as kaolinite, which is commonly present in highly weathered soils, has often been neglected, probably due to the common assumption that negatively charged phyllosilicate minerals have low sorption capacity and binding affinity to IHP and thus do not play any significant role in its fate. Here, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 45 publications
3
23
0
Order By: Relevance
“…Yan et al further suggested that the Al–PO 4 complexes then transformed to surface precipitates with time. A surface precipitation mechanism was also suggested in kaolinite at pH 4 using solid-state NMR . Del Nero et al and Li et al studied phosphate adsorption kinetics on corundum (α-Al 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yan et al further suggested that the Al–PO 4 complexes then transformed to surface precipitates with time. A surface precipitation mechanism was also suggested in kaolinite at pH 4 using solid-state NMR . Del Nero et al and Li et al studied phosphate adsorption kinetics on corundum (α-Al 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…A surface precipitation mechanism was also suggested in kaolinite at pH 4 using solid-state NMR. 31 Del Nero et al 30 and Li et al 29 studied phosphate adsorption kinetics on corundum (α-Al 2 O 3 ). The formation of bidentate binuclear inner-sphere complexes was reported, 29 along with precipitation at high P surface coverage.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Pi, soil Po are an important P pool [42], especially in soils treated with organic inputs [43]. Studies which quantify Po in organic inputs and soils report different values for the amount of Po in soils, ranging from 20 to 90% of the total P pool in soils and sediments [44][45][46][47][48]. A random-effects meta-analysis performed by Darch et al [49], based on different studies, showed that the contribution of Pi and Po to total P varied significantly in organic input or soil (Tables 1-4): for organic input, the contribution of Pi was found to be 5200 mg•kg −1 compared to nearly 4000 mg•kg −1 for the Po pools.…”
Section: Amount and Characteristics Of Po In Soil And Organic Inputsmentioning
confidence: 99%
“…In soils, P forms and amounts vary with soil type [55], land use, and fertilizer history [56]. Given these large pools of Po in soil and fertilizer and the range of values (20-90% of total P) generally contained in soils and sediments [45,48], it is critical to consider Po dynamics along with Pi in order to improve P cycles in agroecosystems. Current understanding suggests that Po is as significant in amount as Pi.…”
Section: Amount and Characteristics Of Po In Soil And Organic Inputsmentioning
confidence: 99%